(untitled) (Journal of Dhaka Medical College, 2020)
Context: Non-steroidal anti-inflammatory drugs (NSAIDs) are most commonly used drugs for years for management of pain and inflammation with good efficacy. NSAIDs are increasingly used for variety of indications like rheumatoid arthritis (RA), osteoarthritis (OA), low back pain (LBP) etc. Prescribing patterns need to be evaluated periodically to increase the therapeutic efficacy, decrease adverse effects and provide feedback to prescribers. A prospective observational study was conducted among patients attending the Out Patient Department (OPD) of Orthopedic and received prescription for NSAIDs in the Mymensingh Medical College Hospital (MMCH) and Community Based Medical College Hospital (CBMCH) in Mymensingh. Material and Methods: The study was carried out on 300 (three hundreds) prescriptions for NSAIDs from orthopedic Out Patient Department (OPD) of Mymensingh Medical College Hospital (MMCH) and Community Based Medical College Hospital (CBMCH). A prospective observational study was conducted from January 2015 to December 2015. Data were collected only from the patients prescribed for NSAIDs and prescribing pattern of NSAIDs were analyzed using SPSS method version 20.1 Results: In case of orthopedic OPD patients most common NSAIDs prescribed to the patients was aceclofenac (29.33%). Others NSAIDs prescribed to the patient in pain management were ketorolac (10%), etoricoxib(8%), ibuprofen (9%), naproxen(9%), sulindac (7%) in orthopedic out patients of both Medical College Hospitals. Most of the NSAIDs were prescribed in brand name (85.34%) where only (14.76%) were prescribed in generic name in both hospitals. Conclusion: From the study it was observed that aceclofenac was the most common NSAIDS used in orthopedic OPD of CBMCH and indomethacin was the most common used NSAIDs in MMCH. Other used NSAIDs were ketorolac, naproxen, etoricoxib, ibuprofen and sulindac. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 195-198